The significance of intellectual property literacy among Malaysian creative industry practitioners - Mohamad Isa, Siti Fariza; Yasin, Megat Al-Imran; Mohammad Razi, Siti Aishah; Mohd Ishan, Zahira (Qualitative Research Association of Malaysia, 2023)
The Malaysian creative industry is the perfect epitome of the representation of a multiracial country that is overflowing with wonderful and rich artistic works. Amidst the copious and palatial creative produce in Malaysia, the industry creative players are not able to generate sustainable income and wealth from their artistic produce due to a lack of knowledge and understanding of intellectual property protection. Empirical data has shown from previous studies indicates the creative industry players are not well-versed in the area of copyright literacy. Due to this, the contents created by the industry players were exploited by capitalist that has greater access to law and policymakers. From this access, the capitalist has more chances of generating incoming compared to creative industry players that are mostly freelancers. Therefore, the wealth that was generated from the creative industry has not benefitted all parties that are involved. The aim of this paper is to explore what are the distinctive elements of copyright protection literacy among creative industry practitioners. The study utilises a qualitative approach, specifically focus group discussion to obtain the data. The results were thematically analysed using ATLAS.ti website version software. The participants for the focus group interview were those invited to a webinar to discuss intellectual property literacy within the Malaysian creative industry. The findings of this paper suggest that the practitioners in the Malaysian creative industry’s intellectual property literacy differ in their position and career that they are in. The implication of the findings from this study is that the understanding and perspective of copyright protection literacy depends on the career and educational background of the industry practitioner involved.